2011
DOI: 10.1016/j.bpj.2010.11.078
|View full text |Cite|
|
Sign up to set email alerts
|

Shear Stress Increases the Residence Time of Adhesion of Pseudomonas aeruginosa

Abstract: Although ubiquitous, the processes by which bacteria colonize surfaces remain poorly understood. Here we report results for the influence of the wall shear stress on the early-stage adhesion of Pseudomonas aeruginosa PA14 on glass and polydimethylsiloxane surfaces. We use image analysis to measure the residence time of each adhering bacterium under flow. Our main finding is that, on either surface, the characteristic residence time of bacteria increases approximately linearly as the shear stress increases (∼0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
125
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 40 publications
7
125
1
3
Order By: Relevance
“…Whereas previous research on surface attachment focused on the effects of high shear rates (10 3 -10 5 s −1 ; ref. 22) and post-attachment dynamics including surface residence time 23 and catch-bond adhesion strength 24 , our results demonstrate that attachment can be enhanced by lower, commonly occurring shear rates with a mechanism virtually independent from specific adhesion properties. For example, P. aeruginosa biofilms are a frequent cause of infection in catheters 3 , where typical shear rates are of the order of 15 s −1 (ref.…”
mentioning
confidence: 75%
“…Whereas previous research on surface attachment focused on the effects of high shear rates (10 3 -10 5 s −1 ; ref. 22) and post-attachment dynamics including surface residence time 23 and catch-bond adhesion strength 24 , our results demonstrate that attachment can be enhanced by lower, commonly occurring shear rates with a mechanism virtually independent from specific adhesion properties. For example, P. aeruginosa biofilms are a frequent cause of infection in catheters 3 , where typical shear rates are of the order of 15 s −1 (ref.…”
mentioning
confidence: 75%
“…Previous studies have shown that shear stress increases the duration of adhesion of both P. aeruginosa and Escherichia coli biofilms to coated surfaces. 30,31 This reduction in the amount of bacteria seen on the ETTs in the in vitro model could be an effect of changes in the physical properties of the biofilm in reaction to shear stress. 32 High shear forces have been shown in the literature to favor the creation of tight, rounded microcolonies of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…There is precedence for mechanotransduction in eukaryotes, in which surface substrate recognition is an important regulator of development and behavior (11). In prokaryotes, surface mechanical forces affect the binding affinity of cells to substrates (12,13) and alter the rotation of flagella (14,15). However, the effects of mechanical forces on cell behaviors other than motility are not understood, and the regulation of virulence by mechanical cues has not been explored.…”
mentioning
confidence: 99%